2016
DOI: 10.1080/15548627.2016.1179403
|View full text |Cite
|
Sign up to set email alerts
|

SESN2/sestrin 2 induction-mediated autophagy and inhibitory effect of isorhapontigenin (ISO) on human bladder cancers

Abstract: Isorhapontigenin (ISO) is a new derivative of stilbene isolated from the Chinese herb Gnetum cleistostachyum. Our recent studies have revealed that ISO treatment at doses ranging from 20 to 80 μM triggers apoptosis in multiple human cancer cell lines. In the present study, we evaluated the potential effect of ISO on autophagy induction. We found that ISO treatment at sublethal doses induced autophagy effectively in human bladder cancer cells, which contributed to the inhibition of anchorage-independent growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 40 publications
2
88
0
Order By: Relevance
“…The results from the present study discovered that MIR516A targeted 3ʹ-UTR of PHLPP2 mRNA, which downregulates its protein translation in human BC; therefore, we defined the novel mechanism of MIR516A regulating PHLPP2 protein translation. Due to the complexity of autophagy, it has been shown to function as a double-edged sword that either protect or suppress human bladder cancer, depending on the stimuli of autophagy, the stage of cancer, and the downstream mediators or effectors [47,48]. Our recent studies have shown that autophagic responses mediated by SESN2/Sestrin 2 mainly result in autophagic inhibition of human bladder cancer cells [48], whereas ATG7-mediated autophagic responses promote growth and invasion of human bladder cancer cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…The results from the present study discovered that MIR516A targeted 3ʹ-UTR of PHLPP2 mRNA, which downregulates its protein translation in human BC; therefore, we defined the novel mechanism of MIR516A regulating PHLPP2 protein translation. Due to the complexity of autophagy, it has been shown to function as a double-edged sword that either protect or suppress human bladder cancer, depending on the stimuli of autophagy, the stage of cancer, and the downstream mediators or effectors [47,48]. Our recent studies have shown that autophagic responses mediated by SESN2/Sestrin 2 mainly result in autophagic inhibition of human bladder cancer cells [48], whereas ATG7-mediated autophagic responses promote growth and invasion of human bladder cancer cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…Human BC cell lines, UMUC3 and T24, were used and are described in our previous studies 49, 50, 51, 52. These cells were maintained in DMEM-F12 (1:1) (Invitrogen) supplemented with 5% heat-inactivated fetal bovine serum (FBS), 2 μM L-glutamine, and 25 μg/mL gentamycin.…”
Section: Methodsmentioning
confidence: 99%
“…The normal bladder cell line UROtsa and human BC cell lines T24T, UMUC3 were described in previous studies [51][52][53][54]. For the details of reagents, cell lines, and cell culture, see the Supplement of "Materials and Methods".…”
Section: Reagents Cell Lines and Cell Culturementioning
confidence: 99%